6 Chemoenzymatic Dynamic Kinetic Resolution of Alcohols - Kanomata,K.; Akai,S. (Dynamic Kinetic Resolution (DKR) and Dynamic Kinetic Asymmetric Transformations (DYKAT), 2023)
Chemoenzymatic dynamic kinetic resolution is one of the simplest and most reliable methods to obtain optically pure alcohol derivatives from racemates. For this purpose, hydrolases, especially lipases, have been widely used in the enantioselective esterification processes, and a variety of racemization catalysts with high catalytic efficiency and compatibility with lipases have been developed. This review introduces chemoenzymatic DKR of alcohols based on the category of racemization catalysts. DKR of axially chiral hydroxybiaryls and the use of engineered lipases to obtain opposite enantiomers, as well as the synthetic applications of the DKR products, are also discussed.
Keywords: Referencework; lipase; hydrolase; racemization; asymmetric synthesis; total synthesis; alcohols; acylation; esterification; dynamic kinetic resolution; enantioselectivity; ruthenium; oxovanadium